Interactive learning and the new technologies : a report of the Educational Research Workshop held in Eindhoven, the Netherlands, 2-5 June 1987 /: a report of the Educational Research Workshop held in Eindhoven, the Netherlands, 2-5 June 1987. (1988) - Unknown
No abstract available